Academic identity status and psychological well-being among medical sciences students - Reza Dastjerdi; Zahra Farshidfar; Mohammadreza Haji-abadi (Mashhad University of Medical Sciences, 2022)
Background: Identity formation is regarded as the most important issue during adolescence. The present study aimed to assess the role of academic identity status in psychological well-being.Method: This descriptive correlation study was conducted on medical sciences students admitted to Birjand University of Medical Sciences in 2017. The statistical population included 600 cases out of whom 240 subjects were selected via the simple random sampling method. Two questionnaires were employed for data collection: Isaacson's academic identity, and Ryff's scale of psychological well-being. The data were analyzed in SPSS (version 19) using descriptive statistics and stepwise regression.Results: The achieved identity was positively and significantly correlated with the variables of relationships with others, self-acceptance, and independence (P<0.05). The diffused identity had a significantly negative correlation with self-acceptance and positive relationship with others. Moratorium identity was significantly and negatively associated with self-acceptance. Furthermore, the correlation between foreclosed identity and self-acceptance was positive and significant.Conclusion: As evidenced by the results of the current study, successful identity contributes greatly to various dimensions of psychological well-being; therefore, family, school, and media perform a major educative role in the provision of appropriate training during growth and facilitation of search and discovery.